PURIFICATION, CHARACTERIZATION OF GLUTATHIONE S-TRANSFERASE FROM THE LIVER TISSUE OF GOOSE (Anser anser Domesticus) AND INHIBITION EFFECTS OF SOME METAL IONS AND CHEMICALS - Yesim SAYIN; Emrah YERLIKAYA; Ramazan DEMIRDAG (Journal of Animal and Plant Sciences, 2024)
The GST enzyme is an antioxidant that protects organs against toxic substances. It reduces reactive oxygen species to less reactive metabolites.The GST enzyme has been studied in many living creatures such as sheep, birds, fish, bacteria, cattle, plants and humans. However, no studies on the Goose (Anser anser Domesticus) liver GST enzyme (E.C. 2.5.1.18) have been found in the literature. This study demonstrates the purification and characterization of the GST enzyme from Goose (Anser anser Domesticus) liver tissue by affinity chromatography. Besides, inhibitory effects of Hg2+, Ag2+ and Fe2+ cations and Oxytetracycline HCl, Tylosin Tartrate, Enrofloxacin and Doxycycline Hyclate chemicals on GST enzyme activity were investigated. The research was conducted under in vitro conditions using 1-Chloro-2,4-dinitrobenzene method. The degree of purity of the enzyme solution was verified by SDS-PAGE. With the characterization of the enzyme, the optimal pH, optimal ionic strength and optimal temperature values were found to be 7.0, 100 mM and 40 °C, respectively. Separate inhibition graphs of Hg2+, Ag2+, Fe2+, Oxytetracycline HCl, Tylosin Tartrate, Enrofloxacin and Doxycycline Hyclate inhibitors were drawn. IC50 levels of inhibitors were found from the Activity% - [Inhibitor] graphs. As a result, the inhibition order of the inhibitors was found to be Hg2+ > Ag2+ > Fe2+ for cations, and Enrofloxacin ˂ Tylosin Tartrate ˂ Doxycycline Hyclate ˂ Oxytetracycline HCl for chemicals.
Keywords: Affinity; Antioxidant; Goose; Nutrient; GST